MAKANAN ETNIK MELAYU: TEMPOYAK - Amanda Haruminori; Nathania Angelia; Andrea Purwaningtyas (Universitas Andalas, 2017)
Traditional food is considered as one of the identities that makes a nation, and it is caused by the varieties of cultures. Tempoyak (asam durian) is one of the examples of traditional foods, specifically for the Malayan ethnic, and it is widely known in Palembang. The majority of Palembang citizens are known to be nomads, and since durians are abundant in Sumatra, food processing is done to increase shelf life. Tempoyak is the result of fermenting durian for 3-7 days by adding salt into the fruit. Fermentation is one of the many ways of food processing. The fermentation of durian gives tempoyak a unique flavour that combines sourness from the fermentation process and sweetness from the fruit itself. Fermentation is one of the most well-known food processing in Indonesia, and has been known for years. To the Malayan ethnics, tempoyak has a unique taste that can increase ones appetite, and it is usually used as a complementary food for rice, and also spices. One of the foods that use a tempoyak spices is brengkes.